Cultura e identidad organizacional de los empleados de la empresa Hielosnorte SAC, distrito de Moche, Trujillo, 2021 - Roncal García, Brenda Belén (2022)
The purpose of this research is to analyze the relationship between the culture and organizational identity of the workers of the Hielosnorte SAC Company, in the district of Moche, Province of Trujillo, through the different elements of organizational culture such as values, norms, forms of communication, leadership and organizational climate. Ethnographic, inductive-deductive and statistical methods were applied, as well as interview and survey techniques mainly. Among the main results, it was found that there is a general tendency of the workers towards the knowledge of the values, norms, stories that make up the organizational culture, but that there is also a lack of adaptation of these to the new forms of work. On the other hand, it is recognized that although the forms of communication, leadership and the organizational climate may be correct for the company, many of the employees do not recognize themselves through them, also due to certain inadequacies.